Studies on growth and Characterization of urea-doped diglycine picrate (DGP) single crystals - Balasundari, N; Selvarajan, P; Ponmani, S.Lincy Mary; Jencylin, D (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Urea-doped diglycine picrate (DGP) single crystals were grown by solution method with slow evaporation technique. The solubility of the urea-doped DGP was carried out at various temperatures and it is observed that the solubility of urea-doped DGP is higher than that of pure DGP crystal. When urea was added as dopant, morphological alterations were noticed in DGP crystal. Cell parameter values of the grown urea-doped DGP crystal were obtained from the XRD analysis and the presence of functional groups was identified from FTIR study. Dlectric studies were performed for the grown crystals and it is found that the values of dielectric constant and loss for urea-doped DGP crystal are more than those of pure DGP crystal. The Vickers microhardness values were measured for the grown crystals. From the microhardness study, it is observed that urea- doped DGP crystal is harder than pure DGP crystal.